An Electronic and Web-Based Authentication, Identification, and Logging Management System (Journal of Engineering, 2024)
The need for participants’ performance assessments in academia and industry has been a growing concern. It has attendance, among other metrics, is a key factor in engendering a holistic approach to decision-making. For institutions or organizations where managing people is an important yet challenging task, attendance tracking and management could be employed to improve this seemingly time-consuming process while keeping an accurate attendance record. The manual/quasi-analog approach of taking attendance in some institutions could be unreliable and inefficient, leading to inaccurate computation of attendance rates and data loss. This work, therefore, proposes a system that employs embedded technology and a biometric/ web-based application to enhance attendance management. The hardware encompasses the integration of an ESP8266 NodeMCU and the biometric AS608 fingerprint sensor interfaced with the database for which the front-end and back-end integration was through the React framework. The system uses a web application that displays the attendance results and scheduled course data from its database, provides feedback to lecturers on which student missed classes and calculates a student’s average attendance for the semester. By implementing this system, the accuracy of student attendance is expected to experience an appreciable improvement, eliminate proxy signing, provide a more secure alternative for attendance recording, curtail tardiness to classes, and ultimately improve student productivity on execution.